In Vitro Efficacy of Ebselen and BAY 11-7082 Against Naegleria fowleri - Debnath, Anjan; Nelson, Andrew T.; Silva-Olivares, Angélica; Shibayama, Mineko; Siegel, Dionicio; McKerrow, James H. (Frontiers in Microbiology, 2018)
Primary amebic meningoencephalitis (PAM) is a fatal infection caused by the free-living ameba Naegleria fowleri, popularly known as the “brain-eating ameba". The drugs of choice in treating PAM are the antifungal amphotericin B and an antileishmanial miltefosine, but these are not FDA-approved for this indication and use of amphotericin B is associated with severe adverse effects. Moreover, very few patients treated with the combination therapy have survived PAM. Therefore, development of efficient drugs is a critical unmet need to avert future deaths of children. Since N. fowleri causes extensive inflammation in the brain it is important to select compounds that can enter brain to kill ameba. In this study, we identified two central nervous system (CNS) active compounds, ebselen and BAY 11-7082 as amebicidal with EC50 of 6.2 µM and 1.6 µM, respectively. The closely related BAY 11-7085 was also found active against N. fowleri with EC50 similar to BAY 11-7082. We synthesized a soluble ebselen analogue, which had amebicidal activity similar to ebselen. Transmission electron microscopy of N. fowleri trophozoites incubated for 48 h with EC50 concentration of ebselen showed alteration in the cytoplasmic membrane, loss of the nuclear membrane and appearance of electron-dense granules. Incubation of N. fowleri trophozoites with EC50 concentrations of BAY 11-7082 and BAY 11-7085 for 48 h showed the presence of large lipid droplets in the cytoplasm, disruption of cytoplasmic and nuclear membranes and appearance of several vesicles and chromatin residues. Blood-brain barrier permeable amebicidal compounds have potential as new drug leads for Naegleria infection.